Revision of fleas of the genus Plocopsylla belonging to the "angusticeps-lewisi" complex in the Andean biogeographic region, with the description of a new species - Sánchez, Juliana Patricia (2015)
In Argentina, the Andean biogeographic region accommodates the most diverse population of fleas in the country. The Craneopsyllinae (Siphonaptera: Stephanocircidae) represent one of the most commonly found subfamilies in this region and show some endemism and high diversity. Plocopsylla is the most diverse genus of Craneopsyllinae; it includes 10 species mainly distributed in the Patagonian subregion, which parasitize sigmodontine rodents (Rodentia: Cricetidae). We describe and illustrate the morphology of the aedeagus in species of Plocopsylla that belong to the 'angusticeps-lewisi' complex. This character is of diagnostic value in differentiating among species. A new species of this complex, Plocopsylla (Plocopsylla) linardii sp. n., is described and identified by the shape and chaetotaxy of the distal arm of sternite IX, as well as by the shape of the median dorsal lobe of the aedeagus. New host associations for this complex and range extensions for most of its species are reported. Plocopsylla (P.) silewi is recorded for the first time in Argentina. The southern limits of the distributions of Plocopsylla (P.) lewisi and Plocopsylla (P.) wilesi are extended to Santa Cruz Province. The angusticeps-lewisi complex is found for the first time in San Juan Province. The information may be useful in epidemiological studies of flea-borne diseases.